The Influence of Capital Structure and Profitability on Firm Value: A Quantitative Study of Food & Beverage Companies Listed on the IDX (2022–2024) - Fadillah, Bintang; Harimurti, Fadjar; Sarwono, Aris Eddy (Golden Ratio of Data in Summary, 2025)
This study investigates the impact of capital structure and profitability on firm value in food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. Capital structure is represented by the Debt to Equity Ratio (DER), profitability by the Return on Assets (ROA), and firm value by the Price to Book Value (PBV). The research employed a quantitative approach using secondary data from the financial reports of 10 selected companies, analyzed through simple linear regression with classical assumption tests. The results revealed that DER had no significant effect on PBV (p = 0.615), whereas ROA had a significant positive effect on PBV (p = 0.000, R² = 0.395). These findings suggest that profitability is more critical in enhancing firm value than capital structure. The study provides practical insights for investors and corporate managers to improve operational efficiency and increase firm value.